2004
DOI: 10.3346/jkms.2004.19.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Systemic Lupus Erythematosus in Patients with Myasthenia Gravis following Thymectomy: Two Case Reports

Abstract: We report two cases of systemic lupus erythematosus (SLE) in myasthenia gravis (MG) patients who had undergone thymectomy. SLE developed in the patients 3 months or 13 yr after thymectomy, and polyarthritis was the main clinical manifestation of SLE. Both patients fulfilled at least four of the revised criteria for the classification of SLE. In this report, we describe two postthymectomy lupus patients and perform a comparative review of previous cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…18 Other studies have reported polyarthritis, skin rashes, fever and cytopenias to be more common in SLE patients with thymoma. 19 Thus, it seems that although the exact mechanisms underlying both pathologies have yet to be elucidated, the association between thymoma and SLE is not incidental. 20,21 Acquired pure red cell aplasia may present as an acute self-limited disease, secondary to viral infection or drug-induced impairments, or as a chronic autoimmune form that may be associated with thymoma.…”
Section: Autoimmune Diseases and Thymomamentioning
confidence: 99%
“…18 Other studies have reported polyarthritis, skin rashes, fever and cytopenias to be more common in SLE patients with thymoma. 19 Thus, it seems that although the exact mechanisms underlying both pathologies have yet to be elucidated, the association between thymoma and SLE is not incidental. 20,21 Acquired pure red cell aplasia may present as an acute self-limited disease, secondary to viral infection or drug-induced impairments, or as a chronic autoimmune form that may be associated with thymoma.…”
Section: Autoimmune Diseases and Thymomamentioning
confidence: 99%
“…In thymectomized MG patients, hypergammaglobulinemia, B cell hyperactivity were observed with mild T cell lymphopenia [6,9,10]. This mechanism was accused of the coexistence of MG and SLE.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of thymectomy on the precipitation of SLE is still controversial [6]. In thymectomized MG patients, hypergammaglobulinemia, B cell hyperactivity were observed with mild T cell lymphopenia [6,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many of these patients had high titres of a variety of autoantibodies, including anti-dsDNA, and anti-cardiolipin antibodies [10,11].…”
Section: Discussionmentioning
confidence: 99%